Measurement, modelling, and evaluation of computing systems and dependability and fault tolerance : 16th International GI/ITG Conference, MMB & DFT 2012, Kaiserslautern, Germany, March 19-21, 2012. Proceedings - Schmitt, Jens B. (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 16th International GI/ITG Conference on Measurement, Modeling and Evaluation of Computing Systems and Dependability and Fault Tolerance, MMB & DFT 2012, held in Kaiserslautern, Germany, in March 2012. The 16 revised full papers presented together with 5 tool papers and 5 selected workshop papers were carefully reviewed and selected from 54 submissions. MMB & DFT 2012 covers diverse aspects of performance and dependability evaluation of systems including networks, computer architectures, distributed systems, software, fault-tolerant and secure systems.